Impact of Graphene/Nanocellulose on Nanocomposite Membrane for Methylene Blue Dye Removal and Antifouling Performance - Rezaur, Rahman; Ain Zaienah, Sueraya; Khairul Anwar, Mohamad Said; Murtala, Namakka; Anthonette, James; Ismail Md. Mofizur, Rahman; Muneera S. M., Al-Saleem; Jehan Y., Al-Humaidi; Mohammed Muzibur, Rahman (John Wiley & Sons, Inc., 2025)
The development of membrane technologies in improving water purification systems has been extensively studied by many researchers to ensure efficient production of clean water sources. However, fouling of PVDF membrane results in low permeation and dye removal efficiency, causing a major issue in membrane production. To mitigate this issue, graphene (GR) and nanocellulose (NC) were incorporated in PVDF membrane to improve the membrane performance, as both nanoparticles have unique hydrophilicity properties and high mechanical strength. The nanocomposite membranes were fabricated via phase inversion method with PVDF as the polymer and N‐methyl‐2‐pyrrolidone (NMP) as the solvent. The nanocomposite membranes were characterized by using field emission scanning electron microscopy equipped with energy dispersive x‐ray spectroscopy (FESEM‐EDX), x‐ray diffraction (XRD